To Heaven or to Hell : Bartolomé de Las Casas's Confesionario - Orique, David Thomas, O.P., 1959- (Book collections on Project MUSE., 2018)
"The first complete English translation and annotated study of Bartolome de Las Casas's 1552 Confesionario. Explores its history and its guidelines for confessors administering the sacrament of confession to conquistadores, encomenderos, slaveholders, settlers, and others who had harmed indigenous peoples"--Provided by publisher.